Novel therapeutic regimens against Helicobacter pylori: an updated systematic review - Huang, Ting-Ting; Cao, Yong-Xiao; Cao, Lei (Frontiers in Microbiology, 2024)
Helicobacter pylori (H. pylori) is a strict microaerophilic bacterial species that exists in the stomach, and H. pylori infection is one of the most common chronic bacterial infections affecting humans.Eradicating H. pylori is the preferred method for the long-term prevention of complications such as chronic gastritis, peptic ulcers, gastric mucosa-associated lymphoid tissue lymphoma, and gastric cancer. However, first-line treatment with triple therapy and quadruple therapy has been unable to cope with increasing antibacterial resistance. To provide an updated review of H. pylori infections and antibacterial resistance, as well as related treatment options, we searched PubMed for articles published until March 2024. The key search terms were 'H. pylori', 'H. pylori infection', 'H. pylori diseases', 'H. pylori eradication" and 'H. pylori antibacterial resistance". Despite the use of antimicrobial agents, the annual decline in the eradication rate of H. pylori continues. Emerging eradication therapies, such as the development of the new strong acid blocker vonoprazan, probiotic adjuvant therapy, and H. pylori vaccine therapy, are exciting. However, the effectiveness of these treatments needs to be further evaluated. It is worth mentioning that the idea of altering the oxygen environment in gastric juice for H. pylori to not be able to survive is a hot topic that should be considered in new eradication plans. Various strategies for eradicating H. pylori, including antibacterials, vaccines, probiotics, and biomaterials, are continuously evolving. A novel approach involving the alteration of the oxygen concentration within the growth environment of H. pylori has emerged as a promising eradication strategy.